(untitled) (Revista Brasileira de Contabilidade e Gestão, 2018)
Exercising business management is related to the set of tools and decisions aimed at maximizing results as well as meeting human needs. Currently, it is necessary to converge management and production (of goods and services and profits) with the precepts of sustainable development (different dimensions). In this sense, the research presented has the problem of answering the following question: the managers of business organizations in the Alto Vale do Itajaí (Santa Catarina) region understand the different dimensions of sustainability? The present text initially makes a theoretical discussion, based on a procedure of exploratory bibliographical research, about theories of administration and sustainable development. In addition, the interview technique was used to collect the data and, in order to reflect on them, the content analysis was used. As a result, it was verified that: i) among the interviewed managers, the relationship between sustainability and "ecology" is still recurrent (only); ii) discourse based on generalizations. Finally, it is emphasized that practicing and implementing (integrated) actions that contribute to sustainable development is the greatest value for the client and for society.